2019
DOI: 10.1038/s41593-019-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the mouse brain endothelial transcriptome in health and disease models reveals a core blood–brain barrier dysfunction module

Abstract: Blood vessels in the central nervous system (CNS) form a specialized and critical structure, the blood-brain barrier (BBB). We present a resource to understand the molecular mechanisms that regulate BBB function in health and dysfunction during disease. Using endothelial cell enrichment and RNA sequencing, we analyzed the gene expression of endothelial cells in mice, comparing brain endothelial cells to peripheral endothelial cells. We also assessed the regulation of CNS Users may view, print, copy, and downlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
341
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(357 citation statements)
references
References 48 publications
16
341
0
Order By: Relevance
“…Given that gene expression programs and gene synergy determine the cellular function to respond to external signals and to carry out complex cellular activities, high-throughput sequencing technologies are now in place to discover gene expression programs and explore the biological mechanism that they govern. Existing genomic profiling studies for cerebrovascular cells use the marker-based method to isolate a single type of vasculature cells for further sequencing (Munji et al, 2019). However, distinct cell types in BBB have their own unique functions and perform highly coordinated actions to keep the central nervous system (CNS) homeostasis (Zhao et al, 2015); therefore, it is important to accurately distinguish different vascular components in the brain to explore the potential function in BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Given that gene expression programs and gene synergy determine the cellular function to respond to external signals and to carry out complex cellular activities, high-throughput sequencing technologies are now in place to discover gene expression programs and explore the biological mechanism that they govern. Existing genomic profiling studies for cerebrovascular cells use the marker-based method to isolate a single type of vasculature cells for further sequencing (Munji et al, 2019). However, distinct cell types in BBB have their own unique functions and perform highly coordinated actions to keep the central nervous system (CNS) homeostasis (Zhao et al, 2015); therefore, it is important to accurately distinguish different vascular components in the brain to explore the potential function in BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to understand how each of the individual cell types in the NVU responds to potentially harmful stimuli, such as drugs or toxins. While extensive brain cell-specific proteome mapping has been carried out recently in mice [1][2][3] these data do not directly translate to the human NVU as proteomic analysis of whole isolated vessels from human and mouse cortices demonstrated large…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, mTBI can elicit a complex sequence of cellular cascades, and lead to genomic responses and transcriptional changes in vascular cells [52], including vascular endothelial growth factor A (VEGFA) [53], and compensatory changes in the extracellular matrix proteins and expansion of the basal lamina [24,44], which not only alter the basement membrane structure and perivascular space but also affect brain infiltration of peripheral leukocytes. Recent evidence from RNA sequencing of brain endothelial cells in different animal models has demonstrated that similar vascular gene expression profiles exist among multiple neurodegenerative diseases including TBI [54], suggesting perhaps that the molecular signature of vascular impairment might be common. Nevertheless, future studies exploring vascular associated transcriptomic changes at single-cell level in both mouse models and human patients are necessary for defining the exact microvascular molecular signature in mTBI, and beyond.…”
Section: Discussionmentioning
confidence: 99%